The effect of a 12-week functional training program on functional - Bieniec, A.; Grabara, M. (Biomedical Human Kinetics, 2024)
Study aim: This study examined the effects of a 12-week functional training (FT) program on basic movement patterns and dynamic balance in hockey players.